Perancangan Film Animasi 3 Dimensi Berjudul “Jangan Menyerah” dengan Metode Pose to Pose - Antasena, Aria; Bustomi, Tommy; Metandi, Farindika (Publica Scientific Solution, 2022)
3D animation film is a development of 2D animation which is developed through computer technology which is growing rapidly. However, in using computer technology to design a 3D animated film that is still very rigid, it can affect the performance of the animation because the animation does not look real like humans and objects. The purpose of this study is to explain the design of animating an animated film using the method that has been made, namely pose to pose for each pose used based on the animation design that has been made for the film entitled